The Islamic right to divorce and its impact on the Muslim community: a case of the Kano state government initiative on divorcees and widows / Magaji Chiroma ... [et al.] - Chiroma, Magaji; Kwagyang, Garba Umaru; Musa Buba, Tijani (2014)
Among the fundamental objectives of marriage in Islam is to have peace, tranquility and sexual satisfaction. This can only be achieved if and only if the marital relationship between the spouses has been properly maintained. Although in Islamic law, it is the right of spouses to terminate the marital relationship, however, that does not aimed at encouraging divorce amongst spouses, as it is always having a negative impact on the society. Thus, the rampant cases of divorce and termination of marriages as a result of supervening circumstances in some of the Muslim communities affects the moral and social behavior and control of the people, which consequently contributes to moral decadence in the society. Hence, it is against this backdrop, the Kano state government in Nigeria intensified efforts and commitments to minimize if not prevent the menace thereby bringing some good initiatives in its administrative policies. To this end, the paper, by making reference to the Kano state government initiative on Divorcees and widows, juxtaposes the Islamic right of divorce on one part and the needs to maintain a marital relationship between spouses for the betterment of the society on the other part.